PARP-1 as a novel target in endocrine-resistant breast cancer - Azzurra Zicarelli; Marianna Talia; Muriel Lainé; Rosamaria Lappano; Marcello Maggiolini; Geoffrey L. Greene (Journal of Experimental & Clinical Cancer Research)
Abstract Background Several mechanisms are involved in the resistance to endocrine therapy (ET) in estrogen receptor (ERα)-positive breast cancer (BC), including acquired mutations of ERα gene (ESR1). For example, the frequent mutation, Y537S, was shown to trigger a constitutively active receptor leading to reduced affinity for both agonist and antagonist ligands. The development of more comprehensive therapies remains a challenge in BC patients exhibiting activating mutations in ERα. Here, we show that Poly (ADP-ribose) polymerase-1 (PARP-1) may be considered as a novel therapeutic target in ERα-positive BC. Methods ERα wild type or Y537S mutated MCF7 and T47D BC cell lines were used as model systems. Immunoblotting, immunofluorescence, gene silencing, real-time PCR, promoter assays, chromatin immunoprecipitation sequencing (ChIP-seq) as well as cell viability, colony and cell cycle assays served to investigate the involvement of PARP-1 in BC progression. The growth of MCF7 ERα Y537S cells injected into the mammary ducts of NSG mice and treated with the ERα antagonist lasofoxifene or the PARP-1 inhibitor niraparib was monitored by luminescence imaging, weight measurement, and histological analysis. RNA sequencing studies were performed on the above-described xenograft tumors. METABRIC dataset was used to evaluate the clinical significance of PARP-1 and the biological role of the PARP-1-associated genes in ERα-positive BC patients. Results We first demonstrated that the up-regulation of PARP-1 expression induced by estrogens is abrogated either by inhibiting or silencing ERα in MCF7 and T47D BC cells expressing ERα wild type or Y537S mutation. We then showed that PARP-1 is involved in the binding of ERα and its co-activator FoxA1 to the promoters of several target genes, as determined by ChIP-sequencing studies. Of note, the inhibition of PARP-1 prevented the proliferative effects mediated by ERα in BC cells expressing either wild type or Y537S ERα. In accordance with these findings, the growth of xenograft tumors derived from MCF7 ERα Y537S BC cells was significantly reduced using niraparib and lasofoxifene. Finally, RNA-sequencing analyses showed that ERα signaling is downregulated by niraparib compared to vehicle-treated tumors. Conclusions Overall, our results suggest that PARP-1 should be explored as a potential target in comprehensive therapeutic approaches in ET-resistant BC.